If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 6 = 0 Reorder the terms: 6 + 2z = 0 Solving 6 + 2z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2z = 0 + -6 2z = 0 + -6 Combine like terms: 0 + -6 = -6 2z = -6 Divide each side by '2'. z = -3 Simplifying z = -3
| -27=18-9u | | 2x+4x^3+4xy^2=0 | | 8x=1-0.33 | | 40+63= | | 9(8+m)=8+9m | | 5z+12= | | -5(x)=2x-5 | | 8x=1-0.67 | | 10x-2(x-1)=10 | | t=y+5 | | 5x-2-4x+1=10 | | 5(p-2)-(2p+2)=12 | | 2(3b-4)=2(r-4)-6 | | 0(x)=2x-5 | | Z/5-7=7/8 | | b(3)=b(2)+1 | | -9+8q=-41 | | 6-6r^2=-195 | | (4.47)(4^2)(3.14)1/3 | | -54=9(g-97) | | 1/2COS^2(5X) | | 75=1/3(3.14)(4^2)H | | h(4^2)(3.14)1/3 | | 68=7(x+4)+5 | | 8a-3=6a+12 | | 21x^2-x^4-80=0 | | -5.91x=-42.14421 | | 4.4y+7.1=6.4y-6.6 | | 8x=0.67 | | 4.7x+8.7=-10.1 | | 6log((x^2)+1)-x=0 | | 8x+xy=1 |